Improvement in overall survival with carfilzomib, lenalidomide, and dexamethasone in patients with relapsed or refractory multiple myeloma - Siegel, David S.; Dimopoulos, Meletios A.; Ludwig, Heinz; Facon, Thierry; Goldschmidt, Hartmut; Jakubowiak, Andrzej; San-Miguel, Jesus; Obreja, Mihaela; Blaedel, Julie; Stewart, A. Keith (Journal of clinical oncology, 2018)
Purpose In the ASPIRE study of carfilzomib, lenalidomide, and dexamethasone (KRd) versus lenalidomide plus dexamethasone (Rd) in patients with relapsed or refractory multiple myeloma, progression-free survival was significantly improved in the carfilzomib group (hazard ratio, 0.69; two-sided P < .001). This prespecified analysis reports final overall survival (OS) data and updated safety results. Patients and Methods Adults with relapsed multiple myeloma (one to three prior lines of therapy) were eligible and randomly assigned at a one-to-one ratio to receive KRd or Rd in 28-day cycles until withdrawal of consent, disease progression, or occurrence of unacceptable toxicity. After 18 cycles, all patients received Rd only. Progression-free survival was the primary end point; OS was a key secondary end point. OS was compared between treatment arms using a stratified log-rank test. Results Median OS was 48.3 months (95% CI, 42.4 to 52.8 months) for KRd versus 40.4 months (95% CI, 33.6 to 44.4 months) for Rd (hazard ratio, 0.79; 95% CI, 0.67 to 0.95; one-sided P = .0045). In patients receiving one prior line of therapy, median OS was 11.4 months longer for KRd versus Rd; it was 6.5 months longer for KRd versus Rd among patients receiving ≥ two prior lines of therapy. Rates of treatment discontinuation because of adverse events (AEs) were 19.9% (KRd) and 21.5% (Rd). Grade ≥ 3 AE rates were 87.0% (KRd) and 83.3% (Rd). Selected grade ≥ 3 AEs of interest (grouped terms; KRd v Rd) included acute renal failure (3.8% v 3.3%), cardiac failure (4.3% v 2.1%), ischemic heart disease (3.8% v 2.3%), hypertension (6.4% v 2.3%), hematopoietic thrombocytopenia (20.2% v 14.9%), and peripheral neuropathy (2.8% v 3.1%). Conclusion KRd demonstrated a statistically significant and clinically meaningful reduction in the risk of death versus Rd, improving survival by 7.9 months. The KRd efficacy advantage is most pronounced at first relapse.